In vivo Evaluation of Retinal and Choroidal Structure in a Mouse Model of Long-Lasting Diabetes. Effect of Topical Treatment with Citicoline - Maestroni, Silvia; Preziosa, Chiara; Capuano, Valentina; Spinello, Alice; Zucchiatti, Ilaria; Gabellini, Daniela; Lattanzio, Rosangela; Bandello, Francesco; Zerbini, Gianpaolo (Journal of Ocular Diseases and Therapeutics, 2015)
Recent evidences indicate early, diabetes-driven, retinal neurodegeneration as the origin of diabetic retinopathy. To verify the possibility to prevent the disease, we investigated in a mouse model of type 1 diabetes the effect of long-lasting hyperglycemia on retinal and choroidal structures and, in parallel, we tested the effect of topical treatment with the neuroprotective agent citicoline. Forty wild-type C57B6 mice were included in this study. Diabetes was induced by a single intravenous injection of alloxan. Five animals were considered as sham-treated controls, 15 animals as sham-treated diabetic mice, 5 animals as citicoline-treated controls and 15 animals as citicoline-treated diabetic mice. After eight months of diabetes in vivo analysis of the retina was performed using the Spectralis HRA (Heidelberg Retinal Angiography) + OCT. Neuroretinal abnormalities, in particular a significant narrowing of Retinal Nerve Fiber Layer (19.3 ± 2.2 vs 23.3 ± 2.4, ?m ± SD, p=0.01), Ganglion Cells/Inner Plexiform Layer (54.3 ± 5.1 vs 62.6 ± 4.0, p=0.03), Ganglion Cells Complex (73.9 ± 4.8 vs 83.8 ± 3.4, p=0.003) and Retinal thickness (223.8 ± 3.9 vs 236.7 ± 5.8, p=0.0004) were detected in the diabetic mouse that showed also a significant reduction of Choroidal thickness (67.4 ± 3.3 vs 84.7 ± 1.9, p=0.0001). In line with the hypothesis that neuroprotection might help preventing diabetic retinopathy, neuroretinal but not choroidal (choroid lacks a neuronal component) dysfunctions were prevented by citicoline. Altogether these findings demonstrate that diabetes-driven neuroretinal dysfunctions can be monitored in vivo by OCT in the mouse. Retinal neuroprotection as obtained by topical citicoline protects from these abnormalities suggesting this approach as a possible way to prevent diabetic retinopathy.